The influence of work environment and work facilities on Employee Performance With Work Motivation As an Intervening Variable - Anna, Anna; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: To analyze the effect of work environment, work facilities on employee performance with work motivation as an intervening variable. Design/methodology/approach: This research approach uses quantitative research, Saturated Sampling method, the population in this study is the technical team of the Health Sector of the Surabaya City Investment and One-Stop Integrated Service Office with a total of 40 people, the measurement scale in this study uses a Likert scale, The data analysis used in this study used static methods with SEM PLS modeling. Findings: These findings reveal that work facilities have had no significant influence on employee performance, while the work environment has a significant influence on performance. However, work facilities have a significant influence on employee performance through work motivation as an intervening variable.. Originality/value: This research contributes to understanding the factors that influence employee performance. The results of this study confirm that although work facilities do not have a direct impact on performance. Furthermore, work motivation plays an important role in improving employee performance as a significant intervening variable between work environment and work facilities on performance. Paper type: Research paper